(untitled) - Peale, Norman Vincent (New York, 2003)
n this phenomenal bestseller, “written with the sole objective of helping the reader achieve a happy, satisfying, and worthwhile life,” Dr. Peale demonstrates the power of faith in action. With the practical techniques outlined in this book, you can energize your life—and give yourself the initiative needed to carry out your ambitions and hopes.
Keywords: Sự yên tâm,Sự thành công,Peace of mind,Success; Kitô giáo,Khía cạnh tôn giáo,Kitô giáo,Khía cạnh tôn giáo,Religious aspects,Christianity,Religious aspects,Christianity